Materializing literacies in communities the uses of literacy revisited - Pahl, Kate (Bloomsbury, 2014)
"What is a 'contemporary' understanding of literacy practices? How can 'literacy' be explained and situated? This book addresses literacy practices research, understanding it as both material and spatial, based in homes and communities, as well as in formal educational settings. It addresses a need to update the work done on theoretical literacy models, with the last major paradigms such as critical literacies and multiliteracies developed a decade ago. Kate Pahl draws on case studies to highlight experiences alternate from the traditional representations of literacy. She argues that the affordances of home and familiar spaces offer fertile ground for meaning-making. These resultant literacies are multimodal and linked to space, place and community. An important evaluative resource, this book details a range of methodologies for further researching literacy, describing ethnographic, visual, participatory and ecological approaches, together with connective ethnographies. This volume will appeal to academics and professions in literacy studies and language and education"--